Contact network modelling for the infectious disease spread predictions - Liu, Wanrui (Nanyang Technological University, 2022)
CoronaVirus Disease 2019 (COVID-19), due to its extremely high infectivity, has been spreading rapidly around the world, impacting socioeconomic developments as well as the daily lives of billions of people. As such, it will be meaningful to be able to model and study the transmission of COVID-19 in crowded spaces and the effectiveness of safety measures such as wearing masks properly and social distancing. In the past decade, various computer models for crowd movement have been developed and can be used to identify health and safety issues. State-of-the-art models that simulate the spread of epidemics operate on a population level, but the collection of fine-scale data might enable the development of models for epidemics that operate on a microscopic scale, similar to models for crowd movement.